Beyond learning by doing: an exploration of critical incidents in outdoor leadership education. Issue 1 (2nd January 2016) - Hickman, Mark; Stokes, Peter
Abstract : This paper argues that outdoor leader education and training is characterized by the development of procedural skills at the expense of crucial but usually ignored non-technical skills (e.g. contextualized decision-making and reflection). This risks producing practitioners with a potentially unsophisticated awareness of the holistic outdoor environment impeding the development of links between theory and practice. This paper analyses the application of critical incident theory to a study of undergraduates in a UK outdoor leadership degree programme in order to examine the processes of developing non-technical reflective skills in the students. The study examines a range of critical incidents in a purposive homogeneous sample of students who were asked to identify and reflect on critical incidents in practice settings of their own choice. These settings spanned from the United Kingdom to remote locations overseas. Qualitative data analysis was carried out using interpretative phenomenological analysis. The findings indicated that outdoor leadership programmes need to develop a broader and holistic skills base rather than concentrate on primarily physical and technical skills. A focus on the critical incident method early in education has the potential to equip practitioners with the holistic and complex set of skills required in the contemporary outdoor workplace.